On somewhat near continuity and some applications - Ameen, Zanyar (2021)
We give more properties and applications to the class of somewhat nearly continuous functions introduced by Piotrowski. Among the applications, we show that the Baire property is preserved under somewhat nearly continuous quasiopen injection images and Baire spaces are preserved under somewhat nearly continuous quasiopen countable fiber complete preimages. The later statement generalizes the results given by Noll, and Mirmostafaee and Piotrowski.